Spatial distribution and determinants of newbornsnot receiving postnatal check-up withintwodays after birth in Ethiopia: a spatial and multilevel analysis of EDHS 2016 - Destaye Guadie Kassie; Nega Tezera Assimamaw; Tadesse Tarik Tamir; Tewodros Getaneh Alemu; Masresha Asmare Techane; Chalachew Adugna Wubneh; Getaneh Mulualem Belay; Amare Wondim Ewuntie; Bewuketu Terefe; Adiss Bilal Muhye; Bethelihem Tigabu Tarekegn; Mohammed Seid Ali; et al. (BMC, 2022)
Abstract Background Accessibility and utilization of postnatal newborn check-ups within 2 days after delivery are critical for a child's survival, growth, and development. However, the service delivery is not yet improved and fluctuates across the geographical locations in Ethiopia. Therefore, this study aimed to assess the spatial distribution and determinants of newborns not received postnatal check-ups within 2 days after birth in Ethiopia. Methods A secondary data analysis of the Ethiopia Demographic and Health Survey (EDHS) 2016 was done among live births within 2 years preceding the survey. A multilevel binary logistic regression model was fitted to identify the factors associated with the outcome variable. Adjusted Odds Ratio with 95% (Confidence Interval) was calculated and used as a measure of associations and variables with a p-value < 0.05, were declared as statistically significant. Results A total of 4036 live newborns in Ethiopia were included in the analysis, of whom half (51.21%) were females. The mean age of the mothers was 33+ SD 1.3, and more than 60 % (61.56%) of the mothers were not educated. The national prevalence of newborns not receiving postnatal check-ups within 2 days after birth was 84.29 (95% CI: 83.10-85.41) with significant spatial variations across the study area. Mothers who had no ANC visits were 58% higher than (AOR = 0.42(0.27-0.66) mothers who had > 4 ANC visits. Mothers who gave birth at home and others were 80% (AOR = 0.02(0.01-0.29) and 25% (AOR = 0.76(0.59-0.99), higher than mothers delivered at hospital. Rural mothers were 1.90 times higher (AOR = 1.90(1.29-2.81) than urban mothers, and mothers live in administrative regions of Afar 66% (AOR = 0.34(0.16-0.69), Oromia 47% (AOR = 0.53(0.30-0.91), Somali 60% (AOR = 0.40 (0.22-0.74),Benishangul 50% (AOR = 0.50 (0.27-0.92), SNNPR 67% (AOR = 0.33(0.19-0.57), Gambela 70% (AOR = 0.30 (0.16-0.56), Harari 56% (AOR = 0.44 (0.25-0.78), and Dire Dawa70% (AOR = 0.30 (0.17-0.54) were higher than Addis Abeba for not receiving postnatal checkup of new born within the first 2 days, respectively. Conclusions Low postnatal check-up utilization remains a big challenge in Ethiopia, with significant spatial variations across regional and local levels. Spatial clustering of not receiving postanal check-ups within 2 days was observed in Afar, Oromia, Gambela, Benishangul, SNNPR, Harari, and Dire Dawa regions. Residence, ANC visits, place of delivery, and administrative regions were significantly associated with not receiving postnatal check-ups. Geographically targeted interventions to improve ANC follow-up and institutional delivery should be strengthened.